Cocreating the Arab Spring: Understanding Transformation of Service Systems in Contention. (August 2015) - Skålén, Per; Aal, Kotaiba Abdul; Edvardsson, Bo
This article examines the transformation of service systems through actors' resource integration and value cocreation in contention. It is based on a netnographic study focusing on the use of information and communications technology (ICT) tools by online activists during the "Arab Spring." The transformation of service systems is conceptualized on the basis of existing service research and on the theory of strategic action fields. Focusing on Syria, the findings suggest that activists transformed four interdependent service systems—the media, the social movement, health care, and the financial service systems—during the Arab Spring by means of integrating resources and cocreating value within several ICT tools. A key contribution to transformative service research is the fact that the positive transformation of service systems derives from the conflict between two types of actors, namely, incumbents and challengers. This article also contributes to our knowledge of triggers of service system transformation, what motivates actors to transform service systems, how service system transformation is enabled by actors' integration and use of ICT tools serving as opportunity spaces, and the transformative roles actors adopt. In addition, this article contributes to the conceptualization of service systems and to the understanding of resource integration and value cocreation.